Balancing usability and aesthetic elements in universities’ website: a systematic review - Habee Bullah Affandy,; Azham Hussain,; Maslinda Mohd Nadzir, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Website is the first line of interactions between the universities and the patrons may it be the students, staff or the public. The usage of internet within universities has increased in this few years. More formal interactions are done through the universities websites or portals. Due to the increased use of the universities website, it has resulted in the importance of proper web design to ensure that the universities have an effective website. Thus, it is important that the design of the website be properly done to ensure effective use of the website and properly reflects the image of the Universities. One of the challenges in designing an effective website is ensuring good web usability and pleasing web aesthetics. Using SLR (Systematic Literature Review), this paper gathers the area of study regarding overall description of a quality website, website usability, web usability measurement, website aesthetics, web aesthetic measurements and to know whether there is the research regarding relationship between web usability and web aesthetics. This study was based on 658 papers gathered from the online library such as IEEE, ACM, Science Direct and Emerald Insight by using a search strategy that has been constructed in the research method. After the filtering process was done based on the inclusion and exclusion criteria, only 78 relevant papers are chosen as the body of knowledge of this study.